The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1063/5.0137698
|View full text |Cite
|
Sign up to set email alerts
|

The role of biomechanical factors in models of intervertebral disc degeneration across multiple length scales

Daniela Lazaro-Pacheco,
Mina Mohseni,
Samuel Rudd
et al.

Abstract: Low back pain is the leading cause of disability, producing a substantial socio-economic burden on healthcare systems worldwide. Intervertebral disc (IVD) degeneration is a primary cause of lower back pain, and while regenerative therapies aimed at full functional recovery of the disc have been developed in recent years, no commercially available, approved devices or therapies for the regeneration of the IVD currently exist. In the development of these new approaches, numerous models for mechanical stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 158 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Mechanical stimulation profoundly influences the synthesis and degradation processes of the IVD. Multiple studies have demonstrated that both supraphysiological loading and repetitive and complex loading have been implicated in the process of disc degeneration 17,18 . In our previous study, in vitro organ culture of bovine caudal discs was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical stimulation profoundly influences the synthesis and degradation processes of the IVD. Multiple studies have demonstrated that both supraphysiological loading and repetitive and complex loading have been implicated in the process of disc degeneration 17,18 . In our previous study, in vitro organ culture of bovine caudal discs was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Intervertebral disc (IVD) degeneration has a lifetime prevalence of up to 80% and is associated with the development of back pain [1,2]. IVD degeneration has a substantial worldwide burden, estimated to affect 266 million individuals annually, leading to significant health care costs and lost wages [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%